Franciscan Learning, Preaching and Mission, c. 1220-1650: Cum scientia sit donum Dei, armatura ad defendendam sanctam fidem catholicam - Roest, Bert (The Medieval Franciscans, 2015)
In this volume, Bert Roest discusses many issues pertaining to the organization of learning in the Franciscan order, and the ways in which this order engaged in pastoral and missionary activities in confrontation with the rise of Protestantism